Exploiting Human Memory B Cell Heterogeneity for Improved Vaccine Efficacy - Pauli, Noel T.; Henry Dunand, Carole J.; Wilson, Patrick C. (Frontiers in Immunology, 2011)
The major goal in vaccination is establishment of long-term, prophylactic humoral memory to a pathogen. Two major components to long-lived humoral memory are plasma cells for the production of specific immunoglobulin and memory B cells that survey for their specific antigen in the periphery for later affinity maturation, proliferation, and differentiation. The study of human B cell memory has been aided by the discovery of a general marker for B cell memory, expression of CD27; however, new data suggests the existence of CD27- memory B cells as well. These recently described non-canonical memory populations have increasingly pointed to the heterogeneity of the memory compartment. The novel B memory subsets in humans appear to have unique origins, localization, and functions compared to what was considered to be a “classical” memory B cell. In this article, we review the known B cell memory subsets, the establishment of B cell memory in vaccination and infection, and how understanding these newly described subsets can inform vaccine design and disease treatment.